A History of Modern Linguistics From the Beginnings to World War II - McElvenny, James ca. 20./21. Jh (Edinburgh University Press, 2024)
Offers a new perspective on the history of linguisticsOffers a concise history of modern linguistics up to World War IIExamines the connections between linguistics and neighbouring fields, including philosophy, psychology and anthropologyFocuses on historical figures in linguistics, and the social and political contexts that shaped their ideas and methodsProvides extensive suggestions for further readingIn this book, McElvenny offers a concise history of modern linguistics from its emergence in the early nineteenth century up to the end of World War II. Written as a collective biography of the field, it concentrates on the interaction between the leading figures of linguistics, their controversies, and the role of the social and political context in shaping their ideas and methods.While A History of Modern Linguistics focuses on disciplinary linguistics, the boundaries of the account are porous: developments in neighbouring fields - in particular, philosophy, psychology and anthropology - are brought into the discussion where they have contributed to linguistic research